Randomized Controlled Trial of Treatments for Loss-of-Control Eating Following Bariatric Surgery - Grilo, Carlos M. (Obesity (Silver Spring), 2021)
BACKGROUND: Loss-of-control (LOC)-eating post-operatively is a consistent predictor of suboptimal longer-term bariatric surgery outcomes. This randomized controlled trial (RCT) examined the effectiveness of two guided-self-help treatments (cognitive-behavioral therapy [gshCBT] and behavioral weight-loss [gshBWL]) to a control (CON) for reducing LOC-eating and weight. METHODS: 140 patients with recurrent LOC-eating six months after bariatric surgery were randomly assigned (5:5:2 ratio) to one of three conditions: gshCBT (N=56), gshBWL (N=60), or CON (N=24). Three-month treatments were delivered by trained allied-health clinicians to increase generalizability to bariatric-surgery settings. Independent assessments were performed by doctoral research-clinicians using established interviews/measures; post-outcomes were obtained for 89% of patients. RESULTS: Mixed-models revealed significant improvements for LOC-eating frequency and weight-loss but no significant differences between treatments; race neither predicted (main-effect) nor moderated (interaction-effect) treatment outcomes. ITT categorical analyses of abstinence from LOC-eating (30% for gshCBT, 27% for gshBWL, 38% for CON) and proportion attaining 5% weight loss (20%, 22%, 17%) revealed no significant differences between treatments; non-White participants had higher proportion achieving LOC-eating abstinence but lower proportion attaining 5% weight-loss than White participants. CONCLUSIONS: In this 12-week RCT following bariatric surgery, significant LOC-eating reductions and weight-loss did not differ significantly between treatments. Race was associated with post-treatment categorical outcomes.